'Informatization' of industry and society: The third industrial revolution. (4th August 2014) - Altenpohl, Dieter G.
'Informatization' is a generic term that covers a range of simultaneous developments in science, technology, industry and administration which have far–reaching social and political implications. The development of informatization is linked with a number of technological developments: the miniaturization and falling cost of electronics; the integration of such techniques as telecommunications and computing; the widespread effect of these changes in industry, administration, and public and private life. This paper reviews the areas in which the impact of informatization is evident, and attempts to assess its long–term implications for both industry and society as a whole.